Emergent cesarean section in a preterm pregnant woman with severe COVID-19 pneumonia in Taiwan: A case report - Chien-Hui Lau; Chih-Lin Mao; Yin-Kuang Chang; Sheng-Kang Chiu; Chou-Chin Lan; Lu-Lu Zhao; Han-Yu Lin; Su-Cheng Huang; Hsiao-Chen Chiu (Elsevier, 2022)
Objective: The pandemic Coronavirus Disease 2019 (COVID-19) is a global public health crisis. Many maternity units worldwide are currently establishing the management protocols for these patients. Case report: We report the first critically ill pregnant woman with COVID-19-induced respiratory failure undergoing emergent caesarean delivery at 32 weeks of gestation, in the setting of a positive pressure operating room (OR) with negative pressure anteroom in Taiwan. Conclusion: Multidisciplinary planning and collaboration are necessary to achieve satisfactory clinical outcomes in pregnancies with critical COVID-19 pneumonia. The combinations of comprehensive evaluation, timely treatment as well as establishment of rigorous protocol and safe environment for the emergent delivery are important.